The Effectiveness of Android Based Interactive Learning Media in Improving Students Computational Thinking on Heat Material - Roslina; Muhammad Nurwahidin; Herpratiwi; Dina Martha Fitri (Jurnal Penelitian Pendidikan IPA, 2026)
Learning using Android-based interactive learning media can actively engage students in the learning process. This study aims to improve students' computational thinking on heat material at SMAN 3 Kotabumi. The research method used in this study is experimentation. Experimental research is used to find the effect of a particular treatment on another under controlled conditions. The design used in this study was a pretest-posttest control group design. Data collection in this study was conducted during the use of Android-based interactive learning media to improve students' computational thinking on heat material in the learning process. The research subjects were 72 high school students, 36 in the experimental class and 36 in the control class. The results showed that this interactive learning media was quite effective in improving computational thinking skills, as seen from the significant difference between the average posttest scores in the experimental class and the control class based on the results of the Independent Samples Test, Sig. (2-tailed) = 0.00, with a significance level below 0.05. Based on the pretest and posttest data, the average N-Gain score was 0.61, categorized as moderate. Based on the research results and data analysis, the developed product can be used in mathematics learning.